International Society for Heart and Lung Transplantation working formulation of a standardized nomenclature for cardiac allograft vasculopathy—2010 - Mehra, Mandeep R.; Crespo-Leiro, Maria G.; Dipchand, Anne; Ensminger, Stephan M.; Hiemann, Nicola E.; Kobashigawa, Jon A.; Madsen, Joren; Parameshwar, Jayan; Starling, Randall C.; Uber, Patricia A. (The Journal of heart and lung transplantation, 2010)
The development of cardiac allograft vasculopathy remains the Achilles heel of cardiac transplantation. Unfortunately, the definitions of cardiac allograft vasculopathy are diverse, and there are no uniform international standards for the nomenclature of this entity. This consensus document, commissioned by the International Society of Heart and Lung Transplantation Board, is based on best evidence and clinical consensus derived from critical analysis of available information pertaining to angiography, intravascular ultrasound imaging, microvascular function, cardiac allograft histology, circulating immune markers, non-invasive imaging tests, and gene-based and protein-based biomarkers. This document represents a working formulation for an international nomenclature of cardiac allograft vasculopathy, similar to the development of the system for adjudication of cardiac allograft rejection by histology.